58.8k views
1 vote
Prove the identification

Prove the identification-example-1

2 Answers

2 votes
hola!

LHS = cosx/cosx - sinx

= cosx/cosx / cosx/cosx - sinx/cosx

= 1 / 1 - tanx = RHS

Hope this helps you!!!!
User Rogier De Ruijter
by
5.7k points
4 votes
Hi there!

L.H.S. =
(cos \: x)/(cos \: x - sin \: x)

Divide th' whole expression by cos x :-


( (cos \: x)/(cos \: x) )/( (cos \: x)/(cos \: x) \: - \: (sin \: x)/(cos \: x) )


(1)/(1 - tan \: x) = R.H.S.


HENCE PROVED.

~ Hope it helps!
User Caleryn
by
6.4k points